Meckel’s diverticulum with varied clinicopathological presentations: A case series at a rural tertiary care center - Jaya Bagchi Samaddar; Rupsha Dutta Pal; Samaddar, Dwaipayan; Goswami, Bidyut Krishna (Asian Journal of Medical Sciences, 2024)
Meckel’s diverticulum (MD), first documented by Wilhelm Fabricius Hildanus in 1598 as a small bowel diverticulum and later detailed by Johann Friedrich Meckel in 1809, is a remnant of the vitellointestinal duct connecting the fetal gut with the yolk sac. It is a true diverticulum, comprising of all the layers of the bowel wall. The commonly cited “rule of 2s” regarding the diverticulum is: Occurs in 2% of the population, has a 2:1 male-to-female ratio, usually discovered by 2 years of age, located 2 feet from the ileocecal valve, and commonly 2 cm in diameter and 2 inches long. Most Meckel diverticula are benign and are incidentally discovered during autopsy, laparotomy, or barium studies. Vitellointestinal duct lining cell being pluripotent, heterotopic tissues such as gastric, pancreatic followed by others might be found. Common clinical presentation in symptomatic cases is gastrointestinal hemorrhages followed by intestinal obstruction, diverticulitis, cystic abdominal mass, patent umbilical fistula, and neoplasm. Clinical signs and symptoms are non-specific simulating other abdominal emergencies and routine radiology is unable to detect the anomaly in rural peripheral centers. Hence, prompt surgical intervention may be needed in emergency cases. Diverticulectomy or ileal segment resection with end-to-end anastomosis is done. Due to the difficulty of diagnosing a pathologic MD pre-operatively, many surgeons recommend prophylactic diverticulectomy in those found incidentally.